Understanding Students’ Motivations for Choosing the English Language Education Study Program - Yunia, Khansa Qurota; Trisila, Feby Setya; Purwanti, Eko (Universitas Muhammadiyah Yogyakarta, 2024)
Choosing a study program is an important decision that influences students’ academic engagement and future career pathways. In Indonesian higher education, English Language Education Study Programs are primarily designed to prepare prospective English teachers. However, students’ reasons for selecting this program may not always align with its teacher-oriented objectives. This study aims to explore students’ motivations for choosing the English Language Education Study Program from their own perspectives. A qualitative descriptive approach was employed, involving semi-structured interviews with five undergraduate students enrolled in the English Language Education Study Program in a private university in Yogyakarta. The data were analyzed thematically to identify recurring patterns in students’ motivations and experiences. The findings reveal three main themes: students’ interest in the English language as the primary motivation, the influence of external factors such as parental advice and admission circumstances, and a mismatch between the program’s teacher-education orientation and students’ career aspirations. The results indicate that most students chose the program to develop English proficiency rather than to pursue teaching as a long-term career. This study highlights the importance of understanding students’ motivations in order to support clearer program orientation, effective academic guidance, and curriculum development within English Language Education programs.